Fractionation scheme and treatment planning method for early glottic cancer in the United States: Economic impact of different medical decisions. Issue 8 (24th January 2020) - Moore, Assaf; Den, Robert B.; Popovtzer, Aaron; Goldvaser, Hadar; Gordon, Noa; Goldstein, Daniel A.
Abstract: Background: Early glottic cancers are often treated with radiotherapy (RT). We assessed the economic impact of fractionation scheme and planning method for payers in the United States. Methods: A population‐based analysis of the total cost of RT for early glottic cancers in the United States was performed annually. The target population was calculated using the Surveillance, Epidemiology, and End Results database. RT costs were based on 2019 pricing by Medicare. Results: We estimate that 3794 patients with early glottic cancers are treated with RT annually. The cost of RT per patient ranges between US $13 964 and $26 599 by fractionation and planning method. Hypofractionation reduces costs by 9% to 14%, while Intensity‐modulated radiotherapy (IMRT) increases costs by 65% to 72%. IMRT‐based standard fractionation leads to an excess cost of $47 937 076 compared with 3D‐based hypofractionation. Conclusions: 3D‐based hypofractionated RT is the current standard of care. It would be reasonable for public and private payers to consider evidence‐based policies for radiation reimbursement.